فاعلية برنامج إرشادي قائم على التفكير الإيجابي والسلوك التنافسي للحد من الإحباط الرياضي للاعبي الكرة الطائرة جلوس - فرج، محمد جمال علي; أبو زيد، حسن يوسف عبدالله (جامعة بنها - كلية التربية الرياضية للبنين, 2022)
يهدف البحث إلى التعرف على فاعلية برنامج إرشادي قائم على التفكير الإيجابي والسلوك التنافسي للحد من الإحباط الرياضي للاعبي الكرة الطائرة جلوس ويتحقق ذلك من خلال ما يلي: 1-التعرف على مستوى التفكير الإيجابي للاعبين. 2-التعرف على مستوى السلوك التنافسي للاعبين. استخدم الباحثين المنهج التجريبي نظرا لملائمته لطبيعة البحث وتم اختيار مجتمع وعينة البحث بالطريقة العمدية من لا عبى الكرة الطائرة جلوس بجمهورية مصر العربية والمسجلين بالاتحاد المصري الباراليمبى للكرة الطائرة دوري ممتاز 2020 / 2021 حيث بلغ حجم مجتمع البحث (150) لاعبا على مستوى أنحاء الجمهورية حيث بلغت عينة الدراسة الاستطلاعية (30) لاعبا وبلغ حجم العينة الأساسية (18) لاعباً من نادى السلام للمعاقين بمدينة بنها. وبعد جمع البيانات والمعالجات الإحصائية والنتائج التي توصل إليها الباحث أمكن التوصل إلي الأستخلاصات والتوصيات الآتية: -توجد فروق دالة إحصائيا بين القياس القبلي والبعدي لصالح القياس البعدي في مستوى التفكير الإيجابي حيث بلغت نسبة التحسن (59.94) - توجد فروق دالة إحصائيا بين القياس القبلي والبعدي لصالح القياس البعدي في مستوى السلوك التنافسي حيث بلغت نسبة التحسن (70.53). The research aims to identify the effectiveness of a counseling program based on positive thinking and competitive behavior to reduce the sports frustration of seated volleyball players. This is achieved through the following: -Recognize the level of positive thinking of the players. -To identify the level of competitive behavior of the players. The researchers used the experimental method due to its relevance to the nature of the research. The research community and sample were chosen in a deliberate way from volleyball players sitting in the Arab Republic of Egypt and registered in the Egyptian Paralympic Volleyball Federation Excellent League 2020/2021, where the size of the research community reached (150) players at the level of the Republic, where a sample of The pilot study was (30) players, and the size of the basic sample was (18) players from Al-Salam Club for the Disabled in Benha City And the data collection, statistical treatments, and the researcher's findings made it possible to reach the following conclusions and recommendations: -There are statistically significant differences between the pre- and post-measurement in favor of the post-measurement in the level of positive thinking, where the percentage of improvement is (59.94). -There are statistically significant differences between the pre- and post-measurement in favor of the post-measurement in the level of competitive behavior, where the percentage of improvement is (70.53). -There are statistically significant differences between the pre- and post-measurement in favor of the post-measurement in the level of mathematical frustration, where the percentage of improvement is (34.30).
Keywords: الكرة الطائرة -- الأداء الرياضي -- التنافسية الرياضية -- التوقعات السلبية -- علم النفس الرياضي -- مصر